A Smartphone App Effectively Facilitates Mothers’ Mind-Mindedness: A Randomized Controlled Trial - Larkin, Fionnuala; Oostenbroek, Janine; Lee, Yujin; Hayward, Emily; Fernandez, Amy; Wang, Ying; Mitchell, Alex; Li, Lydia Y; Meins, Elizabeth (Wiley, 2023)
The efficacy of a smartphone app intervention (BabyMind©) in facilitating mind-mindedness was investigated in a randomized controlled trial, assigning mothers and their 6-month-olds (N = 152; 72 girls, 146 White) to intervention or active control conditions. Mothers who had received the BabyMind© app intervention scored higher for appropriate (d = .61, 95% CI .28, .94) and lower for non-attuned (d = -.55, 95% CI -.92, -.18) mind-related comments at follow-up (age 12 months), compared with their control group counterparts. Adjusting for missing data did not alter this pattern of findings. Mothers' baseline parental reflective functioning did not moderate these relations. Results are discussed in terms of the benefits of early intervention and exploring the efficacy of the app in more diverse populations.
Keywords: 1701 Psychology; 1702 Cognitive Sciences; Developmental & Child Psychology; 3904 Specialist studies in education; 5201 Applied and developmental psychology